La documentation de la production orale des régions berbérophones de Libye (XIXe et XXe siècles) : le Djebel Nefoussa - Di Tolla, Anna Maria (Les études berbères à l'ère de l'institutionnalisation de tamaziyt: mélanges en l'honneur de Salem Chaker et Abdellah Bounfour, 2021)
Keywords: Linguistique – Djebel Nefousa; Vie intellectuelle – Djebel Nefousa

Documentation du berbère nefusi (Tripolitaine - Libye) : Pour une analyse sociolinguistique des textes du XIXe et XXe siècles. - Di Tolla, Anna Maria (2021)
Keywords: Linguistique – Djebel Nefousa

Ibadi Manuscripts in a European Collection: The Kitāb al-Barbariyya and the Private Papers of Auguste Bossoutrot (1856–1937) - Brugnatelli, Vermondo (Journal of Islamic Manuscripts, 2021)
Within the framework of studies concerning the importance of European manuscript collections for Ibadi history, this article aims at retracing the history of an archive put together by the French scholar Auguste Bossoutrot (1856–1937). This archive gathered a quantity of materials on the Arabic and Berber languages collected during his life. In particular, some of the manuscripts contain parts of a long religious work in Berber (Kitāb al-Barbariyya), discovered in the island of Djerba (Tunisia) among the Ibadi community of the island towards the end of the nineteenth century. This text was firstly discovered and reported to the scientific community by another French scholar, A. De Calassanti-Motylinski (1854–1907), but his untimely death prevented him from publishing it and the whereabouts of the manuscripts that contained it remained unknown until the discovery of Bossoutrot’s papers, which contained the longest extant copy of the work (about 900 pages).
Keywords: Linguistique – Djebel Nefousa